Confronting Religious Violence : A Counternarrative - Warner, Meg; Sacks, Jonathan, 1948-2020; Burridge, Richard A., 1955- (Book collections on Project MUSE., 2018)
"Twelve international experts from a variety of theological, philosophical, and scientific fields address the issue of religious violence in today's world"--Jacket